Multifunctional Coordination Compounds: Design and Properties - Silvio Decurtins (CHIMIA, 1998)
Cleverly designed molecular building blocks provide chemists with the tools of a powerful molecular-scale construction set. They enable them to engineer materials having a predictable order and useful solid-state properties. Hence, it is in the realm of supramolecular chemistry to follow a strategy for synthesizing materials which combine a selected set of properties, for instance from the areas of magnetism, photophysics, and electronics. As a possible approach, host/guest solids which are based on extended anionic, homo- and bimetallic oxalato-bridged transition-metal compounds with two- and three-dimensional connectivities are investigated. In particular, we report herein in detail about their structural properties and their multifunctional characteristics in the area of molecular magnetism and photophysics.